Proceedings of Sixth International Conference on Soft Computing for Problem Solving SocProS 2016, Volume 2 - Deep, Kusum; Bansal, Jagdish Chand; Das, Kedar Nath.; Lal, Arvind Kumar; Garg, Harish; Nagar, Atulya K.; Pant, Millie; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This two-volume book gathers the proceedings of the Sixth International Conference on Soft Computing for Problem Solving (SocProS 2016), offering a collection of research papers presented during the conference at Thapar University, Patiala, India. Providing a veritable treasure trove for scientists and researchers working in the field of soft computing, it highlights the latest developments in the broad area of "Computational Intelligence" and explores both theoretical and practical aspects using fuzzy logic, artificial neural networks, evolutionary algorithms, swarm intelligence, soft computing, computational intelligence, etc.
Spammer Classification using Ensemble Methods over Content-Based Features -- A Modified BPDHE Enhancement Algorithm for Low Resolution Images -- Opposition aided Artificial Bee Colony Algorithm for Digital IIR Filter Design -- Cost Optimization of 2-Way Ribbed Slab Using Hybrid Self Organizing Migrating Algorithm -- A Complete Ontological survey of Cloud Forensic in the area of Cloud Computing -- Optimal Path Determination in a Survivable Virtual Topology of an Optical Network using Ant Colony Optimization -- Parameter Optimization for H.265/HEVC encoder using NSGA II -- PSO Based Context Sensitive Thresholding Technique for Automatic Image Segmentation -- Script Identification from Offline Handwritten Characters using Combination of Features -- Multi-Parameter Retrieval in a Porous Fin using Bi-nary-Coded Genetic Algorithm -- Effectiveness of Constrained Laplacian Biogeography Based Optimization for solving Structural Engineering Design Problems -- Soft Computing Based Software Testing - A Concise Travelogue -- Detection and Mitigation of spoofing attacks by using SDN in LAN -- Landslide Early Warning System Development using Statistical Analysis ofSensors' Data at Tangni Landslide, Uttarakhand, India -- Wearable Haptic Based Pattern Feedback Sleeve System -- Job Scheduling algorithm in cloud environment considering the priority and cost of job -- Automatic Location of Blood Vessel Bifurcations in Digital Eye Fundus Images -- Recommendation System with Sentiment Analysis as Feedback Component -- A second order non-uniform mesh discretization for the numerical treatment of singular two-point boundary value problems with integral forcing function.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence